Implementación del sistema de gestión de seguridad y salud en el trabajo para disminuir riesgos en empresa LA MAMITA HUAMACHUCO 2021 - Quispe Quezada, Elfer Nain (2023)
The main objective of the present investigation was to analyze and diagnose the state of the security management of the transport company LA MAMITA SAC, to determine the necessary measures to be taken to reduce the risks of accidents in the company, all this with the involvement of all areas, achieving the implementation of the security management system. The methodology that followed was to identify and analyze the shortcomings in the safety management system, in order to work together with management to establish objectives and manage their compliance, with the care of workers as the main premise. and the minimization of work accidents. It was possible to determine that the security management system did not have the necessary elements to control the occupational risk agents in the work areas, since it is made up of 8 elements and they do not include all the essentials to achieve effective security management. Likewise, the evaluation of risks present within the processes resulted in an important level of potentiality of these, so to reduce these risks, the Occupational Health and Safety Management System had to be implemented, having as its main tool the Check List of Law 29783, thus obtaining that the risks decrease to a tolerable level, and in turn compliance with the Check List increases by 17%, compared to the initial evaluation.